PERBANDINGAN TANGGUNG JAWAB KARAKTER DAN HASIL BELAJAR DI MEKSIKO DAN INDONESIA DI SMA PERTAMA - Vercaruz, Cesar Antonio Plantel; Septiani, Neni; Fitriani, Rini Siski (EduFisika: Jurnal Pendidikan Fisika, 2023)
This study aimed to determine the influence of responsibility character on the learning outcomes of junior high school students' measurement material. The type of research used is quantitative research. The population in this study is students of Junior High School Adhyaksa 1 Jambi City and Escuela Secundaria Diurna, the sample to be used in this study is determined by purposive sampling method, the instrument used is a questionnaire or questionnaire, and the data analysis technique is using regression. The results showed that the character of responsibility and student learning outcomes in the measurement area was significantly influenced. This research can provide new insights into understanding the importance of character development responsibility in improving student learning outcomes. The implications of this research can be the basis for developing learning strategies that are more effective in enhancing the character of Javanese students and improving the learning outcomes of junior high school students.